Relationships Derived from Physical Properties of Waste Cooking Oil / Diesel Blends and Biodiesel Fuels - Ali, Md Isa; Mohd Jaafar, Faezah (Penerbit Akademia Baru, 2019)
The aim of this study is to estimate mathematical relationships of vital fuel properties that are heating value, density, pour point, cloud point, flash point and viscosity of waste cooking oil/diesel blends and biodiesel fuels. The origin of both waste cooking oil (WCO) and biodiesel (BD) are from palm oil to keep the uniformity of this study. To find the fuel properties, experimentation methods are carried out to acquire data for each blend sample. The samples of blends prepared are ranging from 10% to 100% for both waste cooking oil and biodiesel blend with diesel respectively. From the data of fuel properties obtained, graphs of each fuel property against percentage of blends are plotted. Using Microsoft Excel, mathematical equation for each fuel property for WCO/Diesel and BD/Diesel blends are produced with their respective coefficient of determination denoted as R². The results have shown that the properties of the fuel mainly have polynomial relationships. The equations produced are important because fuel properties are prerequisite as input data for research regarding engine combustion diagnostically and in prediction. From the results obtained, it was also determined that BD blends are of better fuel characteristics than WCO blends because of the positive effects of transesterification.